Issues of Rational Use of Waste in the Production of Building Materials - Abobakirova Zebuniso Asrorovna; Umarov Shodiljon Abdug‘ofurovich (International Journal on Orange Technologies, 2023)
This article presents an analysis of the ways of using glass production waste in the production of concrete with an assessment of the possibility of using glass-grinding clay.The use of modern technological approaches in the molding of products can significantly improve the quality of concrete and increase its conservation of natural resources, the use of waste and glass is to produce concrete with improved properties by adding waste to concrete.